Sleep-Waking Discharge of Ventral Tuberomammillary Neurons in Wild-Type and Histidine Decarboxylase Knock-Out Mice - Sakai, Kazuya; Takahashi, Kazushi; Anaclet, Christelle; Lin, Jian-Sheng (Frontiers in Behavioral Neuroscience, 2010)
Using extracellular single unit recordings, we have determined the characteristics of neurons in the ventral tuberomammillary nucleus (VTM) of wild-type (WT) and histidine decarboxylase knock-out (HDC-KO) mice during the sleep-waking cycle. The VTM neurons of HDC-KO mice showed no histamine immunoreactivity, but were immunoreactive for the histaminergic (HA) neuron markers adenosine deaminase and glutamic acid decarboxylase 67. In the VTM of WT mice, we found waking (W)-specific, non-W-specific W-active, sleep-active, W and paradoxical sleep (PS)-active, and state-indifferent neuron groups. We previously demonstrated in WT mice that only W-specific neurons are histaminergic and that they are characterized by a triphasic broad action potential. In the VTM of HDC-KO mice, we found all these groups of state-dependent and state-indifferent neurons, including W-specific neurons that were characterized by a triphasic broad action potential and a W-specific slow tonic discharge, as in WT mice. The W-specific neurons ceased firing before the onset of EEG synchronization, the first EEG sign of sleep, and remained silent during both slow-wave sleep (SWS) and PS. At the transition from SWS to W, they discharged after the onset of EEG activation, the first EEG sign of W. They either responded to an arousing stimulus with a long delay or did not respond. They therefore presented exactly the same characteristics as those seen in the VTM of WT mice. These data indicate that VTM neurons that would normally contain histamine, but do not (ex-HA neurons), still exhibit the firing properties of W-specific HA neurons.